Single-stage medial plateau elevation and metaphyseal osteotomies in advanced-stage Blount’s disease: a new technique - Baraka, Mostafa M. (J Child Orthop, 2021)
PURPOSE: Surgical treatment in advanced-stage infantile Blount’s disease with medial plateau (MP) depression is challenging. Several osteotomies and fixation methods have been described with no established benchmark. We conducted this study to evaluate the efficacy and safety of a new single-stage technique for acute medial condyle elevation and metaphyseal osteotomies with internal fixation. METHODS: A prospective case series of 19 consecutive patients (21 knees) with severe infantile Blount’s disease underwent a single-stage MP elevation and metaphyseal osteotomies, with internal fixation. The mean age was 10.3 years (8.2 to 13.6) and the mean follow-up was 5.1 years (3.2 to 8.3). The outcome measures included clinical and radiological parameters and patient-reported pediatric outcomes data collection instrument (PODCI) score. RESULTS: The mean PODCI score improved significantly from 50% to 88%. The mean internal tibial torsion improved from -27° to 11°. All cases maintained full knee extension, no limitation in flexion range of movement and no signs of instability or lateral thrust gait. All the radiographic parameters improved significantly; the mean tibiofemoral angle improved from -29° to 7°, the metaphyseal-diaphyseal angle improved from 33.4° to 4.7° and the angle of depressed MP improved from 38.3° to 2.4° (p < 0.001). At the latest follow-up, no cases of deformity recurrence were identified, the final limb-length discrepancy was < 1 cm in all patients. CONCLUSION: Single-stage MP elevation and metaphyseal osteotomies with internal fixation significantly improved the clinical and radiographic parameters and PODCI score in advanced infantile Blount’s disease and precluded the use of external immobilization, with no evidence of deformity recurrence. LEVEL OF EVIDENCE: IV